Coronal microleakage in intact and carious teeth obturated using lateral compaction of gutta-percha - Đeri Aleksandra; Sukara S.; Arbutina R.; Trnić Z.; Gajić N. (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: Coronal microleakage is one of the most important factors for the success and longevity of endodontically treated teeth. Aim: The aim of this study was to evaluate in vitro the coronal microleakage in carious and intact teeth obturated with lateral compaction of gutta-percha using the dye penetration method. Materials and Methods: Forty extracted human teeth were allocated to two groups: Group I consisted of 20 intact teeth (10 single-rooted and 10 multi-rooted) and Group II comprised 20 carious teeth (10 single-rooted and 10 multi-rooted). Root canal preparation was performed using the Step-back technique and copious irrigation with 2.5% NaOCl. All root canals were obturated using lateral compaction and AH Plus endodontic sealer. The teeth were coronally filled with either CAVIT only or the combination of GIC and CAVIT, coated with 2 layers of nail varnish and immersed in 50% AgNO3. Afterwards, the teeth were sectioned mesio-distally using a diamond disc and linear dye penetration was evaluated using a stereo loupe with a micrometer scale at x6 magnification. Results: The results showed dye penetration in 70% of teeth filled with CAVIT and in 10% of teeth filled with GIC+CAVIT. The difference was statistically significant (p<0.05). Conclusion: Based on the obtained results, it may be concluded that the least coronal microleakage was observed in intact teeth temporarily filled with the GIC+CAVIT combination.